Pengaruh Iklan Shopee Big Ramadhan Sale 2023 terhadap Perilaku Konsumtif Berbelanja Produk Fashion Mahasiswa Fikom Unisba - Widiastuti; Erik Setiawan (Bandung Conference Series: Public Relations, 2024)
Abstract. The development of the internet has significantly influenced the consumer behavior of students from the Faculty of Communication Sciences (Fikom) at UNISBA, specifically the 2019 cohort. Online buying and selling platforms, such as Shopee, have impacted tendencies towards impulsive purchasing, extravagance, and purchases driven by emotions or social factors among students. This research aims to identify the effects of exposure to Shopee Big Ramadhan Sale 2023 advertisements on YouTube on the consumptive behavior of fashion product shopping among Fikom UNISBA students. Utilizing the Advertising Exposure Theory Model, this quantitative study involves a simple linear regression analysis to determine the relationship between ad exposure and consumer behavior. The positivism paradigm is applied to a population of 317 students, with a sample of 76 students selected through purposive sampling. Data collection is conducted through questionnaires, and quantitative analysis is performed using SPSS 25. The research results of the T-test, it was found that frequency has a positive and significant influence on consumptive behavior, intensity has a negative and not significant influence on consumptive behavior, while duration does not have an influence on the consumptive behavior of the study. Based on the main hypothesis results, it was found that exposure to Shopee Big Ramadhan Sale 2023 advertisements on YouTube has a positive and significant influence on the consumptive behavior of Fikom Unisba students. Abstrak. Perkembangan internet berpengaruh besar terhadap perilaku konsumtif mahasiswa Fakultas Ilmu Komunikasi (Fikom) UNISBA angkatan 2019. Platform jual beli online, seperti Shopee, memengaruhi kecenderungan pembelian impulsif, pemborosan, dan pembelian berdasarkan emosi atau faktor sosial. Penelitian ini bertujuan mengidentifikasi dampak terpaan iklan Shopee Big Ramadhan Sale 2023 di YouTube terhadap perilaku konsumtif belanja produk fashion mahasiswa Fikom UNISBA. Menggunakan Model Teori Advertising Exposure, penelitian kuantitatif ini melibatkan analisis regresi linear sederhana untuk mengetahui hubungan antara terpaan iklan dan perilaku konsumtif. Paradigma positivisme diterapkan dengan populasi 317 mahasiswa dan sampel 76 mahasiswa yang dipilih melalui purposive sampling. Kuesioner digunakan sebagai alat pengumpulan data, dan analisis kuantitatif dilakukan dengan SPSS 25. Hasil penelitian uji-T didapatkan hasil bahwa frekuensi memiliki pengaruh yang positif dan signifikan terhadap perilaku konsumtif, intensitas memiliki pengaruh negatif dan tidak signifikan terhadap perilaku konsumtif, sedangkan durasi tidak memiliki pengaruh terhadap perilaku konsumtif, berdasarkan hasil hasil penelitian hipotesis utama didapatkan hasil bahwa terpaan iklan Shopee Big Ramadhan Sale 2023 di Youtube berpengaruh positif dan signifikan terhadap perilaku konsumtif mahasiswa Fikom Unisba.